Studies on the Chemical Composition of Sapindus mukorossi Gaerin - Dev, Indra; Guha, S. R. D.; Swaleh, Mohd. (Indian Forester, 1979)
Proximate chemical analysis of the Kernel was carried out in order to obtain the basic information about the type of constituents present. This shows 35.9% crude oil &31.87% of crude protein. Crude oil was further purified and its physic chemical properties were determined. Constituent acids of the oil were identified as arachidic acid, stearic acid, palmitic acid and oleic acid. Behenic &lignoceric acids were identified as trace acids.